#Ebola: Tweeting and Pinning an Epidemic. Issue 2 (15th March 2021) - Guidry, Jeanine P.D.; Meganck, Shana L.; Perrin, Paul B.; Messner, Marcus; Lovari, Alessandro; Carlyle, Kellie E.
ABSTRACT: The Ebola outbreak that started in 2014 had infected 28, 652 people and taken more than 11, 325 lives by spring 2016. Along with this infectious disease pandemic, a pandemic of fear surfaced, especially on social media platforms. Yet little is known about the types of communications, the larger ecological context, and the associated risk perception factors that were present in the social media discussion. This study focused on the social media platforms Twitter and Pinterest and analyzed tweets and pins through the lens of a risk communication theory, the Risk Perception Model, as well as a health behavior theory, the Health Belief Model. Large differences were found in the presence of risk perception variables and health behavior variables between the two platforms, and recommendations for public health practitioners to address fear, anger, and attitudinal biases related to Ebola are included.